A Critical Review on the Book Corona Economy: Resistance Economy in Corona Virus Age - Wahhab Qelich (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The unpleasant effects of the Corona illness outbreak on world economies forced some economists to survey and analyze the effects of Corona illness on the economy. The book “Corona Economy: Resistance Economy in Corona Virus Age” is the first significant book in this subject with the purpose of salvation roads recognition for the Iranian economy with resistance economy review. Among the two criticism axes of structure and content, the paper concludes this book as the aggregation of some viewpoints of economic experts, despite many advantages such as innovative and fluent text, it has some defects. The important defects are disconnection in present flow, snap in publishing before determining the Corona effects dimensions, incorrect format, insufficient usage from global studies, and finally lack of comprehensiveness in analysis and solutions. Therefore, it seems the book cannot reach its goals. The paper suggests correction notes to improve and complete its structure and content.